المعايير البيئية وأثرها على النقل البحري (دراسة ميدانية في المرافئ البحرية السورية) - ناعسه, عبير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The target from the research is to identify the impact of environmental standards on the maritime transport of Syrian ports. The research was based on the analytical descriptive approach . The questionnaires were used in data collection and distributed to 100 managers and employees of the Syrian ports. The main findings of the research were: The impotance of environmental standaras and their application in a manner that prevents environmental pollution has a significant impact on maritime transport. Attention to environmental standars was not as high as required by port manaegement, The international standars governing the operation of the international maritime transport sector in terms of agreements for the prevention of environmental pollution and the disposal of waste resulting from ships have an importance that affects maritime transpot, The management of Syrian ports have to activat and enforce all environmental agreements in manner that prevents pollution . In the light of the results of the researchs presented a number of recommendations that could contribute to improving the work of the port in case of application to make our ports a smart ports , such as Environmental standards to be applied because efficient transport services are necessary to achieve greater competitiveness . هدف البحث إلى التعرف على أثر المعايير البيئية على النقل البحري في المرافئ البحرية السورية . اعتمد البحث على المنهج الوصفي التحليلي حيث استخدم في جميع البيانات استبانة وزعت على 100 من المدراء في جميع المستويات والعاملين الإداريين في المرافئ السورية. ومن أهم النتائج التي توصل إليها البحث: أهمية المعايير البيئية وتطبيقها بشكل يمنع التلوث البيئي له أثركبير على النقل البحري، لكن لم يكن الاهتمام به بالمستوى المطلوب من قبل إدارة المرافئ، وأن المعايير الدولية الناظمة لعمل قطاع النقل البحري الدولي من حيث عقد الاتفاقات لمنع التلوث البيئي، والتخلص من النفايات الناتجة عن السفن لها من الأهمية ما يؤثر على النقل البحري، ولذلك على إدارة المرافئ السورية تفعيل تلك الاتفاقات وتطبيقها بشكل يمنع التلوث. وفي ضوء نتائج البحث قدم الباحث جملة من التوصيات التي يمكن أن تسهم في تحسين عمل المرفأ في حال تطبيقها ولتصبح المرافئ السورية مرافئ ذكية مثل ضرورة تطبيق المعايير البيئية لأن كفاءة خدمات النقل أصبحت ضرورية لتحقيق قدر أكبر من القدرة التنافسية .